Mount Athos – between Autonomy and Statehood - Avramović, Dragutin (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Legal status of the Mount Athos is characterized by many special features that make it internationally unique legal regime. The author analyzes peculiarities of Mount Athos territorial status, legal position of residents and visitors, as well as organization of Mount Athos authorities. The author concludes that the Mount Athos is characterized by a kind of para-sovereignty. Its autonomy involves not only the internal organization, autonomous governance and religious autonomy, but it also includes many elements of secular life of their visitors. Mount Athos has its own, separate legislative, administrative and judicial powers, while the Statute of the Mount Athos has greater legal force than all the other laws of the Greek state, because the state can not unilaterally change its provisions. Having in mind that the wide self-government is vested in church authorities and that the monks have very specific way of living, the author takes a position that the Mount Athos represent `monastic state`, but without statehood. The author also states that the Mount Athos will be faced with many challenges in the context of spreading of an assimilating, universal conception of human rights.